(untitled) (Research, Society and Development, 2022)
Accidents with venomous animals are those caused by animals capable of producing venom and inoculating them. According to the World Health Organization (WHO), this is a public health problem. The proposed objective was to describe the epidemiological profile of cases of accidents by poisonous animals in Minas Gerais (MG), between 2015 and 2017, showing the species of animal that caused the accident, the age range of the affected individuals, health macro-region by notification and evolution of cases. Descriptive, retrospective epidemiological study with a quantitative approach. Data were extracted from SINAN, through access to the Information Technology Department of the Unified Health System (DATASUS). Data collection took place from September 1 to 30, 2021. The population of interest were the cases reported in MG in the period between 2015 and 2017. Data were tabulated in Microsoft Office Excel® and statistically treated using the program Statistical Package for the Social Sciences (SPSS) version 20.0. As it is a public domain bank, it was not necessary to submit the project to the Research Ethics Committee. There was a predominance of the age group from 20 to 59 (58,8%), brown race (49,2%), male (54,8%), in the northern macro region (18,8%), involving scorpions (67,9 %) and high cure percentage (97,1%). Thus, it is necessary to develop strategies to contain the situation, such as promoting health education actions for the population on the subject, the development of standard operational protocols aimed at the prevention and management of accidents with venomous animals.